ANALISIS SISTEM PNBP UNTUK MENINGKATKAN EFEKTIFITAS KINERJA PADA KPPN SURABAYA I - Amallia, Meita; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to see non-tax revenue system by using state revenue module in the State Treasury Service (KPPN) Surabaya I as Authorization Accounting Unit of Regional State General Treasurer can be the right system to improve the effectiveness of the performance and service to the public. using qualitative method is descriptive and by conducting research and comprehending Non-tax revenue system which is used in State Treasury Service (KPPN) Surabaya I. To find out and to comprehend the Non-tax revenue system by using interview method. And to find out the effectiveness of the performance which has been done by analyzing Central Government Financial Statement and the Consolidated Financial Statement of State Treasury Service (KPPN) Surabaya I. The results of this study show that the income from the Non-tax revenue which increased from 2011 to 2012. So the Non-tax revenue which has applied the State revenue module can enhance the effectiveness of the performance in the State Treasury Service (KPPN) Surabaya I.Keywords: Non-Tax Revenue System, State Revenue Module, Performance Effectiveness.